What is the Diagnosis? Qual o Diagnóstico? - Durval Jr, João; Godinho, Jardel; Padilha, Jaqueline (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
A 54 years old woman patient, with complaints of sporadic palpitations, without medication and with a structurally normal heart, presents itself in the clinic where the electrocardiogram, observing prolonged monitoring of the D2 derivation with sensitivity 2N.